2021
DOI: 10.1093/ageing/afab086
|View full text |Cite
|
Sign up to set email alerts
|

Association of life satisfaction with disability-free survival: role of chronic diseases and healthy lifestyle

Abstract: Background this article investigates the association between life satisfaction and disability-free survival, and explores the roles of chronic diseases and healthy lifestyle in this association. Method a cohort of 2,116 functionally independent adults aged ≥60 was followed up to 12 years. At baseline, life satisfaction was assessed with the Life Satisfaction Index A (LSI-A). Disability-free survival was defined as the surviva… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 36 publications
2
3
0
Order By: Relevance
“…Poor sleep quality, PTSD symptoms, restless sleep and loneliness were not significantly associated with incident functional disability. The findings appear to confirm previous results 11 , 12 , 13 , 14 , 15 , 21 of an association between depressive symptoms, lower life satisfaction, and incident functional disability, extending previous knowledge on the relationship between depressive symptoms, lower life satisfaction, and disability onset in an African ageing population. Several mechanisms for the development of functional disability from depressive symptoms include the continuous presence of somatic depressive symptoms, poorer management of chronic medical conditions, and increased health risk behaviours, all of which can contribute directly or indirectly to the decline in ADL disability.…”
Section: Discussionsupporting
confidence: 89%
See 3 more Smart Citations
“…Poor sleep quality, PTSD symptoms, restless sleep and loneliness were not significantly associated with incident functional disability. The findings appear to confirm previous results 11 , 12 , 13 , 14 , 15 , 21 of an association between depressive symptoms, lower life satisfaction, and incident functional disability, extending previous knowledge on the relationship between depressive symptoms, lower life satisfaction, and disability onset in an African ageing population. Several mechanisms for the development of functional disability from depressive symptoms include the continuous presence of somatic depressive symptoms, poorer management of chronic medical conditions, and increased health risk behaviours, all of which can contribute directly or indirectly to the decline in ADL disability.…”
Section: Discussionsupporting
confidence: 89%
“…Poor sleep quality, PTSD symptoms, restless sleep and loneliness were not significantly associated with incident functional disability. The findings appear to confirm previous results [11][12][13][14][15]21 of an association between depressive symptoms, lower life satisfaction, and incident functional disability, extending previous knowledge on the relationship between depressive symptoms, lower life satisfaction, and disability onset in an African ageing population.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…Second, our results show that ACEs are positively associated with a decline in health through a decrease in life satisfaction, which is consistent with several recent studies. The study of Hughes et al ( 46 ) found that early adversity was negatively correlated with life satisfaction, and the OR value of low life satisfaction increased with the number of ACEs, while low satisfaction was significantly correlated with an increase in the number of chronic diseases per year ( 47 ). One possible explanation for the above results is that life satisfaction is a type of cognition and evaluation of subjective wellbeing, which generates positive emotions.…”
Section: Discussionmentioning
confidence: 99%